Gene classification and pattern analysis using data mining and machine learning techniques - Ramisa, Aiman Jabeen; Hossain, Ananna; Islam, Sk Md Injamul; Swadesh, Ponuel Mollah; Islam, Md. Toushif (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.